PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA GAS ELPIJI - Adi Purnama Sriada, I Wayan; Oka Parwata, A A Gede (Kertha Desa, 2013)
Legal protection of consumers of LPG user perspective in the review of the consumer protection law. The problems that arise are how consumers of legal protection from the dangers of exploding LPG LPG gas regulator? And how sanctions for businesses if the explosion in LPG gas regulator?. Writing method using normative methods that are descriptive. The results relating to the protection of consumers against the LPG users are not any specific rules governing the use of LPG gas, therefore the laws that can be used as guidelines is Law No. 8 of 1999 on Consumer Protection. With the BFL's, LPG users can demand legal protection in case of an accident and was given administrative penalties or criminal sanctions to businesses.
Keywords: Legal Protection, Perspective, Consumer, LPG Gas